2021
DOI: 10.1039/d0qm01078b
|View full text |Cite
|
Sign up to set email alerts
|

Porous rGO/ZnSe/CoSe2dispersed in PEDOT:PSS as an efficient counter electrode for dye-sensitized solar cells

Abstract: In this work, we employ simple hydrothermal method to synthesize metal-organic framework (MOF)-derived selenide from reduced graphene oxide (rGO) / structured zeolitic imidazolate framework (ZIF). The resulting MOF-derived selenide ((rGO/ZIF)@Se)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 99 publications
0
27
0
Order By: Relevance
“…The peaks related to C=C bonds display quite a high intensity, while those corresponding to C=O bonds show low intensity. This reveals the formation of graphitic carbon during the selenization process of F [27].…”
Section: Cesmentioning
confidence: 75%
See 2 more Smart Citations
“…The peaks related to C=C bonds display quite a high intensity, while those corresponding to C=O bonds show low intensity. This reveals the formation of graphitic carbon during the selenization process of F [27].…”
Section: Cesmentioning
confidence: 75%
“…For the preparation of f -MWCNT-ZnSe-CoSe 2 , we performed the selenization of f -MWCNT/ZIF-8@ZIF-67 composite based on a previously reported hydrothermal synthesis of CoSe 2 . [27] First, we prepared a selenium (Se) precursor solution by dissolving NaOH (19.2837 g) in 30 mL of deionized (DI) water, then selenium powder Se (1.5427 g) was added and completely dissolved by heating the mixture at 80 • C. Secondly, we dissolved f -MWCNT/ZIF-8@ZIF-67 powder (2.3234 g) in an EDTA-2Na aqueous (aq.) solution (10 mL, 80 mM).…”
Section: Preparation Of F-mwcnt-znse-cosementioning
confidence: 99%
See 1 more Smart Citation
“…[184][185][186][187][188][189][190][191] However, very few research works report their use as CEs in DSSCs. [192][193][194][195][196][197][198] In these reports, most MOF-based metal chalcogenide CEs were prepared via in situ calcination and selenization. [192,193,196,197] Hsu et al [197] were the first to synthesize an MOF-derived chalcogenide in 2014 for use as a CE for a DSSC.…”
Section: Metal-organic Framework (Mof)-based Metal Chalcogenide Ces For Dsscsmentioning
confidence: 99%
“…Their work inspired our team to also synthesize without calcination a bimetallic MOF-derived selenide (rGO/ZnSe/CoSe 2 ) by hydrothermal selenization of rGO/ZIF-8@ZIF-67. [198] This porous rGO/ZnSe/CoSe 2 composite was combined with polystyrene sulfonate-doped poly (3, 4- As it was demonstrated that the use of nickel metal in MOF-based chalcogenides contributes to highly improve their performance as electrocatalysts and supercapacitors, this potential can also be investigated for CE application in DSSCs. [189,199]…”
Section: Metal-organic Framework (Mof)-based Metal Chalcogenide Ces For Dsscsmentioning
confidence: 99%